2008
DOI: 10.1111/j.1440-1673.2008.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive prediction of the degree of liver fibrosis in patients with hepatitis C using an ultrasound contrast agent. A pilot study

Abstract: It has been shown that the severity of hepatic fibrosis in patients with hepatitis C can be predicted non-invasively by measuring intrahepatic circulatory time (IHCT) using a microbubble agent with spectral Doppler analysis. The aim of this study was to assess whether this technique is reproducible using a third-generation microbubble agent and contrast harmonic imaging, which are becoming the standard ultrasound techniques in all radiology departments. Twenty-three untreated patients with hepatitis C, who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The method can also be used to assess the severity of hepatic fibrosis in patients with hepatitis C [3,4,9]. Recently, Searle et al [10], using a latestgeneration UCA, demonstrated significant differences between fibrosis stages 1 and 3 and 1 and 4 in measures of the difference between the hepatic vein and hepatic artery UCA arrival times, although their study population was only 23 patients.…”
Section: Introductionmentioning
confidence: 98%
“…The method can also be used to assess the severity of hepatic fibrosis in patients with hepatitis C [3,4,9]. Recently, Searle et al [10], using a latestgeneration UCA, demonstrated significant differences between fibrosis stages 1 and 3 and 1 and 4 in measures of the difference between the hepatic vein and hepatic artery UCA arrival times, although their study population was only 23 patients.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, there are certain contraindications and adverse events. Some have reported mortality rates after liver biopsy at 3 in 10,000 procedures (4,19,22) . Given the importance of assessing liver fibrosis in hepatitis C patients, coupled with the limitations of biopsy, a non-invasive assessment of liver fibrosis based on laboratory tests (19) and imaging (22) needs to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Some have reported mortality rates after liver biopsy at 3 in 10,000 procedures (4,19,22) . Given the importance of assessing liver fibrosis in hepatitis C patients, coupled with the limitations of biopsy, a non-invasive assessment of liver fibrosis based on laboratory tests (19) and imaging (22) needs to be developed. Imaging methods such as ultrasound, computerized tomography and magnetic resonance imaging can provide useful information on morphological changes in the diseased liver (21,22) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, CEUS-derived time-acoustic intensity curves reflects the tissue-of-interest hemodynamics by measuring the changes of intensity of the harmonic frequencies versus time (Krix 2005). The majority of the previously published CEUS studies in patients with chronic diffuse liver disease places great emphasis on the hepatic artery-tovein time-acoustic intensity curves (Staub et al 2009;Searle et al 2008;Ridolfi et al 2007;Lim et al 2005;Blomley et al 2003;Albrecht et al 1999;Pedersen et al 2005). However, there are limited data to date on liver CEUS perfusion imaging in patients with diffuse liver disease (Kaneko et al 2005) CEUS-related perfusion parameters include time to enhancement (ET), time to peak intensity (PIT), peak signal intensity (PSI), enhancement duration (ED) and area under the curve (AUC).…”
Section: Introductionmentioning
confidence: 99%